Managing Director's Consolidated Multilateral Surveillance Report to the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2011)
The global economy has entered a dangerous phase. Policy makers must act boldly to finish the job they began in 2009, lest the gains from the recovery since then be lost. Collective action can put the global economy on a path to strong, sustainable, and balanced growth.